Peningkatan Kapabilitas Petugas KPPS dalam Penyelenggaraan Pemilu 2024 di Kelurahan Renon melalui Sosialisasi Tugas dan Kewajiban Petugas KPPS: Increasing the Capabilities of KPPS Officers in Organizing the 2024 Elections in Renon Subdistrict through Socialization of the Duties and Obligations of KPPS Officers - Wardani, Kadek Devi Kalfika Anggria; Wijaya, I Gede Rizky Adi; Gorda, Anak Agung Ngurah Eddy Supriyadinata (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
General elections are a process in which citizens freely express their aspirations by choosing potential leaders for the progress of the country. One of the successes of the election is the existence of KPPS officers. Many problems related to KPPS are faced in the field. KPPS is the very tip of the ad hoc body which always attracts attention every election. These problems involve limitations in understanding regulations, technical implementation of voting, and counting votes from the Chairman and Members of KPPS. In this activity, 3 stages are followed, namely planning, implementation, and evaluation. The first planning stage is carried out by interviews and providing solutions by conducting outreach through BIMTEKs. Next, provide an evaluation by giving a pre-test and post-test to determine the understanding of KPPS officers. This activity aims to increase the knowledge of KPPS Officers regarding their duties and obligations as KPPS Officers so that mistakes that occurred in the previous General Election no longer occur. The benefit of implementing socialization through BIMTEK is to improve the quality of holding general elections in Renon Village. The results of the socialization through BIMTEK show that there has been an increase, which was initially 37% after taking part in the socialization through BIMTEK, increasing to 95%.